The hepcidin gene promoter nc.-1010C > T; -582A > G haplotype modulates serum ferritin in individuals carrying the common H63D mutation in HFE gene - Silva, B. (2015)
Hereditary hemochromatosis is an autosomal recessive disorder characterized by severe iron overload. It is usually associated with homozygosity for the HFE gene mutation c.845G > A; p.C282Y. However, in some cases, another HFE mutation (c.187C > G; p.H63D) seems to be associated with the disease. Its penetrance is very low, suggesting the possibility of other iron genetic modulators being involved. In this work, we have screened for HAMP promoter polymorphisms in 409 individuals presenting normal or increased serum ferritin levels together with normal or H63D-mutated HFE genotypes. Our results show that the hepcidin gene promoter TG haplotype, originated by linkage of the nc.-1010C > T and nc.-582A > G polymorphisms, is more frequent in the HFE_H63D individuals presenting serum ferritin levels higher than 300 μg/L than in those presenting the HFE_H63D mutation but with normal serum ferritin levels or in the normal control group.Moreover, it was observed that the TG haplotype was associated to increased serum ferritin levels in the overall pool of HFE_H63D individuals. Thus, our data suggest that screening for these polymorphisms could be of interest in order to explain the phenotype. However, this genetic condition seems to have no clinical significance.